SOUTH AFRICAN PSYCHOLOGY IN HISTORICAL PERSPECTIVE - Kelly, Kevin (PINS-Psychology in Society, 2025)
Van Ommen, C & Painter, D (eds) (2008) Interiors: A history of psychology in South Africa. Pretoria: UNISA Press. ISBN 978-1-86888-448-3 pbk. Pages viii + 485. Interiors is a large 482 page book that consists of sixteen chapters written by 21 authors, some of whom are themselves notable figures in the history of psychology in South Africa. It begins with a chapter by editors Clifford van Ommen and Desmond Painter, on forms of historiography. This is followed by a chapter on the “history of history writing about psychology” in South Africa. The other chapters address a range of topics: scientific racism and professionalisation; critical psychology; behaviourism; psychoanalysis; existential-phenomenological psychology; systemic thinking and cybernetic approaches; psychopathology and colonial experience; research on child development; social psychology; neuropsychology; community psychology; and the theory of the individual in South African psychology.